A General Approach to Dehydro-Freidinger Lactams: Ex-Chiral Pool Synthesis and Spectroscopic Evaluation as Potential Reverse Turn Inducers. - Waibel, Reiner; Gmeiner, Peter; et al. (Journal of Organic Chemistry, 2003)
Starting from natural α-amino acids, a practical synthesis of the dehydro-Freidinger lactams 9a-h based on the ring-closing olefin metathesis reaction was investigated. The presented examples comprise 6-, 7-, 8-, 9-, and 10-membered cyclic dipeptide mimics. Structural variations were demonstrated. We approached the metathesis precursors 8a-h employing an N-alkylation/peptide-coupling strategy. Subsequent ring closure was promoted by the ruthenium-based catalyst 10a or 10b. The resulting tetraresidue 11d was shown to undergo intramolecular hydrogen bonding based on NMR and FT-IR studies. Thus, the development of dehydro-Freidinger lactams as potential reverse turn inducers stabilizing an intramolecular NH i+3⋯CO i hydrogen-bond was demonstrated.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.lphch.agener